Analyst Forecast Errors and Stock Price Behavior Near the Earnings Announcement Dates of LIFO Adopters - Biddle, Gary C.; Ricks, William E. (Journal of Accounting Research, 1988)
Ricks [1982] found that stock returns near the earnings disclosure dates of 1974 LIFO adopters were negative and significantly lower than returns near the earnings disclosure dates of firms not using LIFO. Given that firms adopting LIFO in 1974 were voluntarily switching to an accounting method providing often significant tax savings, it is not obvious why investors would have reacted negatively. Nor is it likely that investors were unaware of many of the firms' LIFO adoption decisions. This study presents evidence suggesting that the negative excess returns observed by Ricks [1982] were associated with, and possibly due to, analysts' systematic overestimates of earnings of firms adopting LIFO in 1974. We are aware of no previous study documenting systematic errors in analysts' earnings forecasts conditional on a voluntary accounting method change.